Biomechaniczna ocena zdolnosci silowych siatkarzy w róznych okresach rocznego makrocyklu treningowego - Sliwa, M.; Sacewicz, T. (Polish Journal of Sport and Tourism, 2015)
Introduction. In order to help volleyball players achieve superior results, their coaches are constantly seeking new training methods. One of the methods used to improve the effectiveness of the training that is being implemented is conducting tests which make it possible to assess the player´s locomotor system in terms of its motor and biomechanical functions. The aim of the study was to determine the torque of the knee flexor and extensor muscles of volleyball players in three stages of the annual macrocycle. Material and methods. The study involved 14 volleyball players. Torque was assessed using the BIODEX System 4 Pro at the angular velocities of 60 °/s and 180 °/s, in three periods of the annual training macrocycle. Results. After the preparatory training period, there was a statistically significant increase in the torque of the flexor and extensor muscles of the lower limbs, both for the lower velocity (p . 0.02 for the right limb and p . 0.024 for the left limb) and the higher one (p . 0.03 for the right limb and p . 0.034 for the left limb). After the preliminary round, statistically insignificant changes were found for the torque values obtained at both velocities. Conclusions. The study showed that frequent monitoring of players can help assess their strength capacity in a more reliable way. The results of such measurements carried out in different periods of the volleyball season can help evaluate the players´s strength at a given moment, verify and modify the training methods which are being used, and approach each player individually.